2008
DOI: 10.1007/s11596-008-0622-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propofol on the mRNA expression of toll-like receptor 4 in BV-2 cells during mimic ischemia-reperfusion injury in vitro

Abstract: This study investigated the effects of propofol on the mRNA expression of Toll-like receptor-4 (TLR4) in BV-2 cells during mimic ischemia-reperfusion (I/R) injury in vitro. BV-2 cells, a mouse microglia line, were cultured and divided into 4 groups at random: control group (group C), ischemia/reperfusion group (group I/R), low-dose propofol (25 micromol/L) intervention group (group PF(25)) and high-dose propofol (100 micromol/L) intervention group (group PF(100)). The mRNA expression of TLR4 and NF-kappaB was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
1
1
Order By: Relevance
“…Although propofol increased the expression of immune cells compared with inhaled anesthetic agents, it significantly increased the apoptosis of lipopolysaccharidetreated mononuclear cells and lymphocytes (25)(26)(27). Many studies have supported a protective effect of propofol against injury through TLR4 (28)(29)(30)(31)(32). The difference in results between propofol and midazolam in the present study was remarkable, although both are GABAergic drugs.…”
Section: Discussioncontrasting
confidence: 44%
“…Although propofol increased the expression of immune cells compared with inhaled anesthetic agents, it significantly increased the apoptosis of lipopolysaccharidetreated mononuclear cells and lymphocytes (25)(26)(27). Many studies have supported a protective effect of propofol against injury through TLR4 (28)(29)(30)(31)(32). The difference in results between propofol and midazolam in the present study was remarkable, although both are GABAergic drugs.…”
Section: Discussioncontrasting
confidence: 44%
“…The expression of TLRs has been detected in microglia as well as astrocytes, and their expression has been shown to be modulated by a variety of internal or external stimuli, including TLR agonists, hypoxia, and proinflammatory cytokines [2 -4], suggesting direct involvement of TLRs in the regulation of CNS inflammation. In both in vivo and in vitro studies, our previous data demonstrated that TLR4 and TLR2 might be involved in brain damage and in inflammation triggered by ischemic injury [5][6][7][8]. They may activate a nuclear factor-kappa B (NF-κB) signaling pathway, thereby resulting in the transcription of many pro-inflammatory genes encoding cytokines, chemokines, proteins of the complement system and aggravating brain damage.…”
mentioning
confidence: 99%